Prevalence of Multidrug Resistant Bacteria in Refugees: A Prospective Case Control Study in an Obstetric Cohort - Oelmeier de Murcia, Kathrin; Glatz, Birgit; Willems, Stephanie; Kossow, Annelene; Strobel, Marlit; Stühmer, Bianca; Schaumburg, Frieder; Mellmann, Alexander; Kipp, Frank; Schmitz, Ralf; Möllers, Mareike (Zeitschrift für Geburtshilfe und Neonatologie, 2017)
Purpose To determine the prevalence of multidrug resistant (MDR) bacteria in a cohort of pregnant refugee women.Methods In a prospective case control study, surveillance cultures for MDR bacteria (methicillin-resistant Staphylococcus aureus [MRSA], vancomycin-resistant enterococci [VRE], MDR Gram-negative bacteria [MRGN]) were analysed between October 2015 and June 2016 from a cohort of 50 pregnant refugee women and 50 resident controls in the obstetric unit of a German tertiary referral hospital.Results Prevalence of MRSA was noticeably higher among refugee women compared to residents (6 vs. 0%). In addition, a trend towards a higher prevalence of VRE and MDR Gram-negative bacteria in refugees was shown (1.8 vs. 0%).Conclusions Due to the higher prevalence of MDR bacteria, surveillance cultures are justified in order to prevent nosocomial spread of MDR bacteria.
Keywords: MRSA; VRE; multidrug resistant Gram-negative bacteria; refugee medical care; hospital hygiene